Anchorage of external reinforcement in the case of rigid clamping. Issue 2 (May 2016) - Luo, Guoqing; Mensinger, Martin
Abstract: In the case of frame bridges with external reinforcement, the reinforcing elements have to be anchored in the abutment wall. Owing to the interaction of negative bending moment and longitudinal shear force in the abutment area, the force transfer between concrete, external steel reinforcement and normal steel reinforcement is complex. Two frame structure tests were carried out to investigate the loadbearing behaviour and rational anchorage length of external reinforcement in abutments. Two different anchorage lengths were tested, and the structural behaviour and failure modes of the two specimens were compared and analysed. The results indicate that the anchorage length has a great influence on the loadbearing capacity, and the pull‐out effect at the end of the external reinforcement should be paid special attention. The detail stress distribution and the M‐V interaction in the anchored external reinforcement were obtained from the tests and the results fit well with the theoretical calculation. Mechanical models are proposed to evaluate the pull‐out effect and optimize the anchorage length of the external reinforcement.